Otra mirada a la catedral: a 50 años de “Property rules, liability rules and inalienability: one view of the cathedral” - Saavedra Velazco, Renzo Esteban (2023)
In April 1972, Guido Calabresi and Douglas Melamed published an article that is unanimously acclaimed as a landmark in the understanding of the legal system. In that paper, the authors identified three rules that discipline legal entitlements, the so-called property rules, liability rules, and inalienability. The difference among them is related to the way in which they allowed the exercise, disposition, and protection of legal prerogatives. Despite the transcendence of this approach, the time elapsed since its publication and the diffusion achieved worldwide by the Law and Economics movement, in Civil Law countries —especially in Latin America— the proposal has not been fully appreciated in its true scope, nor with its subsequent clarifications and criticisms. The purpose of the research is to take Calabresi and Melamed's ideas further to glimpse their utility for the understanding of law, becoming a topic of general legal theory.